2015
DOI: 10.1016/j.ejpoleco.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

So closed: Political selection in proportional systems

Abstract: We analyze political selection in a closed list proportional system where parties have strong gatekeeping power, which they use as an instrument to pursue votes. Parties face a trade-off between selecting loyal candidates or experts, who are highly valued by the voters and thus increase the probability of winning the election. Voters can be rational or behavioral. The former cares about the quality mix of the elected candidates in the winning party, and hence about the ordering on the party list. The latter on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 14 publications
0
42
0
Order By: Relevance
“…The most important first aspect to be measured in evaluating the performance of government is to see how the country's economy runs steadily (Galasso & Nannicini, 2015;Klingeman, 2015;Palea, 2015). It is also important to see the satisfaction of voters, especially young voters, assess how Jokowi-JK government gives satisfaction from economic sector.…”
Section: Resultsmentioning
confidence: 99%
“…The most important first aspect to be measured in evaluating the performance of government is to see how the country's economy runs steadily (Galasso & Nannicini, 2015;Klingeman, 2015;Palea, 2015). It is also important to see the satisfaction of voters, especially young voters, assess how Jokowi-JK government gives satisfaction from economic sector.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, first-time candidates may go straight to the top of the party list, whereas MPs in lower positions do not necessarily become electable. In their the study on Italy, a closed list PR system, Galasso and Nannicini (2015) showed that loyalists, i.e. former MPs or those occupying a party position, are usually allocated to safe positions, while experts, or 'independents', are placed in unsecure positions.…”
Section: Explaining Re-selection: Theoretical Arguments and Hypothesesmentioning
confidence: 99%
“…Voters tend to be important principals in open-list electoral systems, which allow citizens to voice their preferences by selecting individual politicians. Parties gain more importance in closed-list systems and when the parties are responsible for drawing up electoral lists and ranking the candidates who appear on them (Galasso and Nannicini, 2015). The electoral system therefore dictates whether voters and parties have the capacity to act on their desire to punish or reward their agents.…”
Section: Legislative Voting In a Multiple Principal Frameworkmentioning
confidence: 99%